MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL PBL, CTL DAN SCRAMBLE MUATAN IPAS KELAS IV - Siti Ruhama; Wahdah Refia Rafianti (STKIP Subang, 2024)
ABSTRACT Low critical thinking skills and student learning outcomes are caused by one-way learning, unvaried learning models and media, and monotonous learning. Efforts to overcome this by using a combination of PBL, CTL and Scramble models. This study aims to analyze the improvement of critical thinking skills, and learning outcomes. The research was conducted on 19 fourth grade students at SDN Baramban, with the type of PTK research with qualitative and quantitative approaches conducted IV times a meeting. In students' critical thinking skills at meetings I to IV increased with very skillful criteria. And student learning outcomes from a percentage of 42% to 89%. Therefore, the use of a combination of PBL, CTL and Scramble models increased students' critical thinking skills and learning outcomes.